Carl Schmitt utazásai Magyarországra és a magyar jogi gondolkodásba - Techet, Péter (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2025)
The article explores Carl Schmitt’s influence on Hungarian legal science and political public opinion, especially before 1945. On the one hand, it analyses which elements of Schmitt’s theories were discussed in Hungary and why the ‘Großraumlehre’, in particular, attracted significant interest. On the other hand, Schmitt’s two visits to Budapest (1942 and 1943) are briefly described, especially regarding his lecture on ‘The State of European Legal Science’, which was first published in Hungarian and contained connections with conservative-traditionalist Hungarian legal theory.